1919 – a magyar egyetem elűzése Kolozsvárról - Vajda, Tamás (Per Aspera ad Astra, 2020)
The professors of the Cluj-Napoca University – founded in 1872 and funded from the Hungarian state budget – were appointed by the Hungarian head of state from 1872 to 1919, on the proposal of the Hungarian Minister of Religion and Public Education. The university was operating successfully even during World War I. In October 1918, the number of students enrolled at the university was the same as during the pre-war period, and the academic year started as usual. On December 24, 1918, the Romanian army occupied the city of Cluj-Napoca. Subsequently, the Romanian army regularly harassed the professors, many of whom were temporarily imprisoned without a court sentence and a significant war indemnity was imposed on them. Students were prevented from communicating with their families. Between January and April 1919, professors and students were driven to starvation in order to render the university inoperative. On May 9 (13 months before the signing of the official peace treaty), the Romanian prefect ordered professors to swear allegiance to the Romanian king within 72 hours. All teachers refused to do so, citing international conventions. On May 12, within half an hour of the refusal, three hundred armed soldiers forcibly seized the university’s buildings, and all professors were deprived of their jobs. Most of them were physically expelled from the Romanian occupation zone in the autumn of 1919. From January 1920 the teachers of the university temporarily continued their teaching activities in Budapest and from October 1921 in Szeged. The study presents the stages of this process using new historical sources.